The relationship between financial inclusion and entrepreneurship among South African women - Khoza, Maximillan (Department of Finance and Tax, 2025)
In South Africa, women have historically faced multifaceted challenges in accessing financial resources, starting and growing businesses, and achieving economic independence. These challenges have contributed to persisting gender disparities in their economic participation. Given the potential for inclusive financial practices to bridge gender disparities, this study examines women's entrepreneurship to generate practical recommendations for policymakers and practitioners. Secondary quantitative data from the World Bank's Global Findex Database was used, and various statistical methodologies, including correlation and regression analysis, were applied. The nature and strength of the relationships between financial inclusion and entrepreneurship among South African women were analysed to understand the impact of financial inclusion on women's entrepreneurship and the determinants and barriers affecting South African women's entrepreneurial engagement. The findings highlighted a positive correlation between women's entrepreneurial engagement and financial inclusion, implying that the latter can enable the participation of women in entrepreneurial activities. Findings also suggested that there has been a steady increase in women's involvement in savings, investments, and entrepreneurial ventures over time. These findings confirm the significant potential for financial inclusion to empower women economically and facilitate greater participation in entrepreneurship. Policymakers and practitioners can use the insights from this study to develop targeted initiatives and interventions aimed at enhancing financial inclusion and, by extension, empowering women economically.